Diverse mechanisms of IRF5 action in inflammatory responses - Khoyratty, T; Udalova, I (Elsevier, 2018)
Interferon regulatory factor 5 (IRF5) is a key signal-dependent transcription factor in myeloid cells. Its expression is induced by granulocyte-macrophage colony stimulating factor and interferon-gamma. IRF5 protein is further activated in response to stimulation, translocating to the nucleus where it mediates inflammatory responses. IRF5 is capable of both the up-regulation of pro-inflammatory genes and repressing anti-inflammatory mediators, thus polarising macrophages to a pro-inflammatory phenotype. We discuss IRF5 interactions with a wide range of transcriptional regulators that give rise to its diverse effects at the level of chromatin.